Peculiarities of the coherent population trapping resonance in the fluorescence obtained in a coated 87Rb cell in the presence of transverse magnetic field: theory and experiment. (12th January 2018) - Taskova, E; Alipieva, E; Todorov, G
Abstract: We present an experimental and theoretical investigation of the influence of the transverse magnetic field (TMF) on the coherent population trapping resonances obtained on the Zeeman sublevels of the D1 line of 87 Rb in a paraffin-coated vacuum cell. It is shown that a TMF changes the shape and sign of the resonance or destroys it completely. The role of the different rank polarization moments in the integral registered fluorescent signal in the presence of stray magnetic fields is clarified using numerical simulations.